The Relationship between Knowledge and Family Support for Antiretroviral Treatment (ARV) Compliance in HIV/Aids Patients at RSUD dr. Pirngadi Medan - Yunitra Devi (TOUR HEALTH JOURNAL, 2023)
Medication for the exposure to HIV infection is antiretroviral (ARV) therapy which means that curing HIV can be done by some medicines. ARV does not kill virus; it can only slow down its growth. The objective of the research was to analyze the correlation of knowledge and family support with adherence to ARV therapy in HIV/AIDS patients. The research used cross sectional design. It was conducted at RSUD dr. Pirngadi, Medan. The population was 743 patients treated by ARV from January until June, 2018, and 90 of them were used as the samples. The data were gathered by distributing questionnaires, processed by starting by editing, coding, entry, and cleaning the data, ad analyzed by using univariate analysis and bivariate analysis with chi square test. The result of the research showed that there was the correlation of knowledge (p = 0.001) and family support (p = 0.001) with adherence to ARV therapy in HIV/AIDS patients. It is recommended that HIV/AIDS patients adhere to and spend their time in having ARV therapy according to doctors’ orders and not postponing the schedule of ARV therapy.